Development of E-Modules based on STEM Integrated Problem-Based Learning on Acid-Base Materials - Syahkarina Maha; Jasmidi (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aims to determine the development process, level of validity, practicality, and effectiveness of E-Modules based on Problem Based Learning (PBL) integrated Science, Technology, Engineering, and Mathematics (STEM) on acid-base materials in improving cognitive learning outcomes of grade XI high school students. The research method used is Research and Development (R&D) with reference to the 4D development model (Define, Design, Develop, Disseminate). The research was carried out at SMA PAB 6 Helvetia in the second semester of the 2025/2026 Academic Year. The research sample was taken using the purposive sampling technique, namely one class XI Science with a total of 20 students. The data collection instrument consists of expert validation sheets (materials and media), teacher response questionnaires, and test instruments in the form of multiple-choice questions through pre-test and post-test. The data were analyzed quantitatively and qualitatively. The results of the study show that: (1) The Define stage  successfully identified the need for interactive teaching materials,  the Design stage  produced the design  of interactive e-module components  using Flip PDF Professional,  the Develop stage  produced tested products, and  the Disseminate stage  was carried out through the dissemination of flipbook links. (2) The e-module feasibility level  is  declared very valid with an average percentage of material experts of 94.2% and media experts of 94.1%. (3) The level of practicality based on the response of the chemistry teacher obtained a percentage of 98.4% with the category of very practical. (4) The effectiveness test on cognitive learning outcomes showed an increase in the average score from 25.25 in  the pre-test to 77.75 in the post-test, with the achievement of  an N-Gain value  of 0.70 (70%) which is included in the high category and quite effective. Based on these results, it can be concluded that  the STEM-integrated PBL-based e-module on acid-base materials developed has met the valid, practical, and effective criteria for use in chemistry learning in high school. The findings in the development  of STEM-integrated Problem Based Learning (PBL)-based E-Modules  on acid-base materials have a number of competitive advantages as digital learning media. First, this product offers high accessibility where learners can explore material independently through mobile devices (smartphones) without space and time limitations. Second, this E-Module systematically presents contextual problems that are integrated with the four pillars of STEM, so that it is able to stimulate student problem-solving.